ANALYSIS OF APPRAISAL SYSTEM IN NEWS TEXT “MENDIKBUD MINTA KURIKULUM PENDIDIKAN CALON GURU AGAMA DIEVALUASI” - Affandy, Ali Nuke; Widyaiswara, Tiara (Universitas PGRI Sumatera Barat, 2023)
This research analyzes news item on the Kompas.com site related to radicalism and intolerance in education by teacher religion evaluation, to analyze about the news is applied Appraisal Theory that focuses on negotiating social relations about one's assessment of something. This study used qualitative documentation as research design. For data collection techniques used reading and searching for news techniques, selecting research data news according to the formulation of the problem and research objectives, then conducting a language analysis of news taken from Kompas.com using appraisal. Then the data are processed to be able to classify appraisal attitude according to the category. The result study shows the appraisal include projecting source, attitude, graduation, and heterogloss. Finally, the interpersonal meaning concern in graduation focus which imply force intensifier and focus sharpener.